Qualidade de vida e segurança alimentar: estudo de base populacional no município de João Pessoa-PB - Soares, Maria Elma de Souza Maciel (2016)
The quality of life, according to WHO is characterized by its multifactorial nature and includes six main domains: physical health, psychological state, independence level, social relations, environmental characteristics and spiritual standard. Food and nutrition security is the realization of the right to regular and permanent access to quality food in sufficient quantity, without compromising access to other essential needs. To evaluate the quality of life and food security of a population can generate useful information for optimization and development of public policies and to generate comparison of indicators between cities and regions of the country. The objective of this study was to investigate the influence of social factors on the situation of food security and quality of life in João Pessoa city, PB. This is a cross-sectional population-based study, conducted from April to June 2015. The stratified sample consisted of 438 households, where aged over 18 years women were interviewed. A form with characteristics of the socio-demographic profile, WHOQOL-bref and Brazilian scale food and nutrition security were used for data collection. This study revealed an overall mean score of quality of life of 63.3, with a decrease in western and east areas of the city and especially in field environment. Quality of life was significantly associated with household crowding (p = 0.011) and social and leisure activities: watching movie at home (p = 0.045), cinema (p <0.001), museum and theater (p = 0.019), reading (p = 0.024), concert and shows (p <0.001), sport (p <0.001), walks (p <0.001), meeting with friends (p = 0.008), bar (p <0.001), television (p = 0.024 ), radio (p = 0.036) and internet (p <0.001). About food insecurity found a prevalence of 21.7% with statistically significant associations for the variables type of household (p <0.001), agglomeration (p <0.001), water supply (p = 0.027), reading (p = 0.054), sport (p <0.001), walk (p = 0.008), meeting with friends (p = 0.004), bar (p = 0.009), television (p = 0.003), radio (p = 0.003) and internet (p = 0.001). Quality of life were significantly associated with food security situation (p <0.001). The logistic model showed that women in food insecurity has three times less chance to provide a better quality of life. This study showed important information about impact of social determinants of quality of life and food security situation. It is expected that these results can guide managers for development of public policies aimed at ensuring food security, impacting positively on the quality of life.